Optimalisasi Peran Komisi Pemilihan Umum (KPU) dalam Mewujudkan Pemilu yang Demokratis di Indonesia - Ta’mirotul Biroroh; muwahid muwahid (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2021)
The General Election Commission (KPU) is an institution that carries out the function of organizing elections in Indonesia. In addition to the KPU, there are institutions that also play an important role in the implementation of elections and are closely related to the existence of the KPU, namely survey institutions that carry out quick count processes. The survey institutions in a number of developing countries, especially those that are actively building democracy, are also not a little doubted by their moral honesty, at least being sued with a critical attitude such as the existence of a poll on the existence of a political survey institution, which has resulted in an attitude of uncertainty about the performance survey agency. This condition makes people less confident in the survey results which are considered no longer independent. It is proven that every time an election is held, a number of survey institutions seem to want to lead public opinion towards certain contestants. This is certainly very unfortunate considering that the survey results are one of the important instruments in democracy. Abstrak: Komisi Pemilihan Umum (KPU) merupakan lembaga yang menjalankan fungsi sebagai penyelenggara pemilu di Indonesia. Selain KPU, terdapat lembaga yang juga berperan penting dalam pelaksanaan pemilu dan terkait erat dengan eksistensi KPU, yakni lembaga survei yang melakukan proses hitung cepat (quick count). Berbagai lembaga survei yang ada di beberapa negara berkembang yang sedang giat melakukan proses demokratisasi, tidak sedikit yang diragukan kejujuran moralnya di kalangan masyarakat dengan berbagai pandangan dan sikap kritis yang tidak sedikit menghasilkan sikap kegamangan atas kinerja dari lembaga survei tersebut. Kondisi yang ada ini membuat masyarakat kurang memberikan kepercayaan kepada hasil yang diberkan oleh lembaga survei yang dinilai tidak lagi independen. Hal tersebut terbukti dalam berbagai kesempatan dalam penyelenggaraan pemilu, sejumlah lembaga survei yang ada memberikan kesan ingin menggiring opini publik kepada kontestan tertentu. Hal tersebut tentu sangat disayangkan mengingat bahwa hasil survei merupakan salah satu instrumen penting dalam demokrasi.